High-selectivity catalyst for plastic pyrolysis as well as preparation method and application of high-selectivity catalyst

By using cellulose and alumina to prepare highly selective composite catalysts, the problems of low activity, short life and poor selectivity of existing catalysts are solved, and the pyrolysis efficiency of plastics and the improvement of product quality are achieved, which has significant economic benefits and environmental protection.

CN119869498APending Publication Date: 2025-04-25HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510120338.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing catalysts for pyrolysis of plastics have low activity, short service life and poor selectivity, resulting in low pyrolysis efficiency of plastics, poor product quality and high cost.

Method used

Cellulose and alumina are used as main raw materials to prepare highly selective composite catalysts through pore-blanking and calcining steps to improve the activity and selectivity of the catalyst.

Benefits of technology

It significantly improves the pyrolysis efficiency of plastics, improves product quality, improves the yield of aromatic hydrocarbons, reduces production costs, and has significant economic benefits and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869498A_ABST
    Figure CN119869498A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-selectivity catalyst for plastic pyrolysis, which is characterized in that a cellulose-alumina composite catalyst with high selectivity for plastic pyrolysis is prepared by using conventional catalysts alumina and cellulose as main raw materials through unique treatment and composite processes. The catalyst has the advantages of being high in activity, long in service life, good in selectivity and the like, can remarkably improve pyrolysis efficiency, improve product quality and improve the yield of target product aromatic hydrocarbon after being used in the plastic pyrolysis process, accordingly effectively reduces production cost, improves product quality, and has the advantages of being remarkable in economic benefit, good in environmental protection performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, in particular to a high-selectivity catalyst for plastic pyrolysis and a preparation method and application thereof. Background Art

[0002] With the widespread use of plastic products in modern society, plastic waste has become a serious environmental problem. As a relatively environmentally friendly method for treating plastic waste, plastic pyrolysis technology plays an increasingly important role in the treatment and consumption of plastic waste.

[0003] The products of plastic pyrolysis are mainly small molecule gases, hydrocarbons and coke. In the prior art, alumina is usually used as a catalyst to catalyze the pyrolysis of plastics. However, the current catalysts have the following significant defects: 1. Low activity, resulting in large catalyst consumption, low efficiency of plastic pyrolysis process, long pyrolysis time, and incomplete pyrolysis; 2. Short life, resulting in frequent catalyst replacement, low reusability, and high plastic pyrolysis cost; 3. Poor selectivity, resulting in more side reactions in plastic pyrolysis, affecting the purity and yield of the target product, especially the purity and yield of aromatic hydrocarbons with higher economic value. That is, the existing catalysts have many usage defects that seriously restrict and limit the promotion and application of plastic pyrolysis technology.

[0004] Therefore, how to effectively improve the existing catalysts for plastic pyrolysis so that they can effectively select the target product aromatic hydrocarbons during the catalytic plastic pyrolysis process is of great significance for improving the yield of useful target product aromatic hydrocarbons and the pyrolysis efficiency of waste plastics. Summary of the invention

[0005] The technical purpose of the present invention is to use cellulose and aluminum oxide as main raw materials, through a unique processing composite process, to prepare a highly selective composite catalyst for plastic pyrolysis. The catalyst has the advantages of high activity, long service life, good selectivity, etc. After being used in the plastic pyrolysis process, it can significantly improve the pyrolysis efficiency, improve the product quality, increase the yield of the target product aromatic hydrocarbons, and effectively reduce the production cost, with significant economic benefits and good environmental protection.

[0006] In order to achieve the above technical purpose, the technical scheme adopted by the present invention is: a method for preparing a highly selective catalyst for plastic pyrolysis, comprising the following steps: Step 1, weigh wood pulp cellulose or cotton pulp cellulose and aluminum oxide as raw materials in a molar ratio of 1: (3-12) and set aside; Step 2: Soak the wood pulp cellulose and / or cotton pulp cellulose weighed in step 1 in a sodium hydroxide solution, and perform a porous treatment at a temperature of 70-90° C. for 1.5-3 hours. After taking out, rinse with deionized water until neutral, and then transfer to a 55-70° C. environment for drying for 20-25 hours to obtain porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 450-500° C., and calcine for 3-4 hours to obtain impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, and add a silane coupling agent and a cross-linking agent citric acid to the obtained mixed materials in sequence, stir and mix thoroughly, and then drop ammonia water into the obtained mixed materials to adjust the pH value to 8-9, to obtain a reaction sol, which is set aside; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry it at 60-65°C to form a gel, then place the gel in a muffle furnace, set the temperature to 450-500°C, and calcine it for 4-5h to obtain a finished high-selectivity catalyst.

[0007] Furthermore, in step 1, the purity of the wood pulp cellulose or cotton pulp cellulose is not less than 98%.

[0008] Furthermore, in step 1, the purity of the aluminum oxide is not less than 98%.

[0009] Furthermore, in step 2, the mass concentration of the sodium hydroxide solution is 10%, and the sodium hydroxide solution is required to completely submerge the weighed wood pulp cellulose or cotton pulp cellulose.

[0010] Furthermore, in step 2, the temperature of the pore-opening treatment is 80° C., and the treatment time is 2 hours.

[0011] Furthermore, in step 4, the amount of the silane coupling agent added is 2% of the mass of the mixed material.

[0012] Furthermore, in step 4, the amount of the cross-linking agent citric acid added is 6-10% of the mass of the mixed materials.

[0013] Furthermore, in step five, the evaporation drying time is 20-24 hours.

[0014] A highly selective catalyst for the pyrolysis of plastics.

[0015] Application of highly selective catalysts in catalytic pyrolysis of plastics.

[0016] Beneficial effects of the present invention: (1) The method for preparing a highly selective catalyst for plastic pyrolysis of the present invention uses conventional catalyst alumina and cellulose as main raw materials, and prepares a cellulose-alumina composite catalyst for plastic pyrolysis with high selectivity through a unique treatment and composite process. Compared with conventional catalysts in the prior art, the catalyst has the advantages of high activity, long service life, good selectivity, etc. After being used in the plastic pyrolysis process, it can significantly improve the pyrolysis efficiency, improve the product quality, and increase the yield of the target product aromatic hydrocarbons, thereby effectively reducing the production cost and improving the product quality. It has the advantages of significant economic benefits and good environmental protection.

[0017] (2) The method for preparing a highly selective catalyst for plastic pyrolysis of the present invention comprises a step of treating cellulose with a sodium hydroxide solution of a specific mass concentration to make the cellulose porous. The porous treatment can effectively remove substances such as hemicellulose and lignin in wood pulp cellulose or cotton pulp cellulose to change the pore structure of the cellulose, so that the porous cellulose has a special porous loadable structure, thereby achieving effective combination and loading with the impurity-removing aluminum oxide in the subsequent steps, thereby improving the catalytic activity of the finished highly selective catalyst.

[0018] (3) Compared with conventional catalysts in the prior art, the highly selective catalyst for plastic pyrolysis of the present invention has higher catalytic activity and can accelerate the pyrolysis process of plastics, thereby significantly improving the pyrolysis efficiency. The finished catalyst has good selectivity and can selectively convert aromatic hydrocarbons in the product, thereby increasing the yield and purity of fuel oil and other valuable chemicals and effectively improving the product quality. The finished catalyst has a long service life and a high reusability, thereby reducing the processing cost of plastics.

[0019] (4) The method for preparing a highly selective catalyst for plastic pyrolysis of the present invention has simple steps, convenient operation, low catalyst raw material cost, mild operating conditions, less environmental pollution during the process, high yield of effective products, and significant environmental and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The figure is a comparison chart of the catalytic yields of various embodiments of the present invention at different temperatures. DETAILED DESCRIPTION

[0021] The principles and features of the present invention are further described in detail below with reference to examples. However, the following examples are only used to explain the present invention and are not used to limit the scope of the present invention. The operating processes described in the following examples are all carried out at room temperature and pressure unless otherwise specified.

[0022] The present invention provides a composite catalyst with cellulose and aluminum oxide as main raw materials and a preparation process thereof, aiming to improve the pyrolysis efficiency of plastics, improve product quality and reduce production costs.

[0023] The present invention provides a method for preparing a highly selective catalyst for plastic pyrolysis, which specifically comprises the following steps: Step 1: weigh wood pulp cellulose and / or cotton pulp cellulose and alumina with a purity of not less than 98% as raw materials in a molar ratio of 1:(3-12) and set aside; Step 2: soak the wood pulp cellulose or cotton pulp cellulose weighed in step 1 in a sodium hydroxide solution with a mass concentration of 10%, and perform a pore-removing treatment at a temperature of 70-90° C. for 1.5-3 hours to remove hemicellulose and lignin therein and change the pore structure of cellulose. Then take it out, rinse it with deionized water to neutrality, and then transfer it to a 55-70° C. environment for drying for 20-25 hours to obtain a porous cellulose for standby use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 450-500° C., and perform roasting for 3-4 hours to remove impurities, thereby obtaining impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, then add 2% of the mass of a silane coupling agent to the obtained mixture to enhance the binding force, and then add 6-10% of the mass of a crosslinking agent citric acid to the mixture after fully mixing, and use a sol-gel method to fully stir and mix, and then slowly add ammonia water to the obtained mixture to adjust the pH to 8-9 to obtain a reaction sol for standby use; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry at 60-65°C for 20-24h to form a gel, then place the gel in a muffle furnace, set the temperature to 450-500°C, and calcine for 4-5h to obtain a finished high-selectivity catalyst.

[0024] The above-mentioned highly selective catalyst for plastic pyrolysis can be used to catalyze the pyrolysis of plastic.

[0025] The invention discloses a method for preparing a highly selective catalyst for plastic pyrolysis, which solves the problems of low activity, short service life and poor selectivity of existing catalysts. With cellulose and aluminum oxide as main raw materials, a composite catalyst with high activity, long service life and good selectivity for aromatic hydrocarbon target products is prepared through unique process steps and fine process control. After being used in the plastic pyrolysis process, the pyrolysis efficiency can be significantly improved, the product quality can be improved, and the composite catalyst has the remarkable advantages of high aromatic hydrocarbon yield, low disposal cost, remarkable economic benefit, good environmental protection and the like.

[0026] Example 1 The method for preparing a highly selective catalyst for plastic pyrolysis of this embodiment specifically comprises the following steps: Step 1: weigh 10 g of wood pulp cellulose with a purity of not less than 98% and a certain amount of alumina as raw materials in a molar ratio of 1:3, and set aside; Step 2: Soak the wood pulp cellulose weighed in step 1 in 100 ml of a 10% sodium hydroxide solution, perform a pore-removing treatment at 80° C. for 2 hours, then take it out, rinse it with deionized water until it is neutral, and then transfer it to a 65° C. environment for drying for 20 hours to obtain a porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 500° C., and calcine for 3 hours to remove impurities, thereby obtaining impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, then add 2% by weight of a silane coupling agent (3-aminopropyltriethylsilane) to the obtained mixture, mix thoroughly, then add 6% by weight of a cross-linking agent citric acid to the mixture, use a sol-gel method, stir thoroughly, and then slowly drop ammonia water to the obtained mixture to adjust the pH to 8.5 to obtain a reaction sol for standby use; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry at 65°C for 20 hours to form a gel, then place the gel in a muffle furnace, set the temperature to 500°C, and calcine for 4 hours to obtain a finished high-selectivity catalyst.

[0027] Example 2 The method for preparing a highly selective catalyst for plastic pyrolysis of this embodiment specifically comprises the following steps: Step 1: weigh 5 g of wood pulp cellulose and 5 g of cotton pulp cellulose with a purity of not less than 98% and a certain amount of alumina as raw materials in a molar ratio of 1:5, and set aside; Step 2: Soak the wood pulp cellulose weighed in step 1 in 100 ml of a 10% sodium hydroxide solution, perform a pore-removing treatment at 80° C. for 2 hours, then take it out, rinse it with deionized water until it is neutral, and then transfer it to a 60° C. environment for drying for 24 hours to obtain a porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 450° C., and perform roasting for 4 hours to remove impurities, thereby obtaining impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, then add 2% of the mass of a silane coupling agent (3-aminopropyltriethylsilane) to the obtained mixture, mix thoroughly, then add 7% of the mass of a cross-linking agent citric acid to the mixture, use a sol-gel method, stir thoroughly, and then slowly drop ammonia water to the obtained mixture to adjust the pH to 8 to obtain a reaction sol for standby use; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry at 60°C for 24 hours to form a gel, then place the gel in a muffle furnace, set the temperature to 450°C, and calcine for 5 hours to obtain a finished high-selectivity catalyst.

[0028] Example 3 The method for preparing a highly selective catalyst for plastic pyrolysis of this embodiment specifically comprises the following steps: Step 1: weigh 10 g of cotton pulp cellulose with a purity of not less than 98% and a certain amount of aluminum oxide as raw materials in a molar ratio of 1:7, and set aside; Step 2: Soak the wood pulp cellulose weighed in step 1 in 100 ml of a 10% sodium hydroxide solution, perform a pore-removing treatment at 70° C. for 3 hours, then take it out, rinse it with deionized water until it is neutral, and then transfer it to a 55° C. environment for drying for 25 hours to obtain a porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 470° C., and calcine for 3.5 hours to remove impurities, thereby obtaining impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, then add 2% by weight of a silane coupling agent (3-aminopropyltriethylsilane) to the obtained mixture, mix thoroughly, then add 8% by weight of a crosslinking agent citric acid to the mixture, use a sol-gel method, stir thoroughly, and then slowly drop ammonia water to the obtained mixture to adjust the pH to 8.5 to obtain a reaction sol for standby use; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry at 63°C for 23 hours to form a gel, then place the gel in a muffle furnace, set the temperature to 450°C, and calcine for 5 hours to obtain a finished high-selectivity catalyst.

[0029] Example 4 The method for preparing a highly selective catalyst for plastic pyrolysis of this embodiment specifically comprises the following steps: Step 1: weigh 10 g of wood pulp cellulose with a purity of not less than 98% and a certain amount of alumina as raw materials in a molar ratio of 1:9, and set aside; Step 2: Soak the wood pulp cellulose weighed in step 1 in 100 ml of a 10% sodium hydroxide solution, perform a pore-removing treatment at 90° C. for 1.5 hours, then take it out, rinse it with deionized water until it is neutral, and then transfer it to a 70° C. environment for drying for 20 hours to obtain a porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 500° C., and perform roasting for 3.5 hours to remove impurities, thereby obtaining impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, then add 2% of the mass of a silane coupling agent (3-aminopropyltriethylsilane) to the obtained mixture, mix thoroughly, then add 9% of the mass of a cross-linking agent citric acid to the mixture, use a sol-gel method, stir thoroughly, and then slowly drop ammonia water to the obtained mixture to adjust the pH to 8 to obtain a reaction sol for standby use; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry at 65°C for 22 hours to form a gel, then place the gel in a muffle furnace, set the temperature to 450°C, and calcine for 4.5 hours to obtain a finished high-selectivity catalyst.

[0030] Example 5 The method for preparing a highly selective catalyst for plastic pyrolysis of this embodiment specifically comprises the following steps: Step 1: weigh 7 g of wood pulp cellulose and 3 g of cotton pulp cellulose with a purity of not less than 98% and a certain amount of alumina as raw materials in a molar ratio of 1:12, and set aside; Step 2: Soak the wood pulp cellulose weighed in step 1 in 100 ml of a 10% sodium hydroxide solution, perform a pore-removing treatment at 85° C. for 2 hours, then take it out, rinse it with deionized water until it is neutral, and then transfer it to a 60° C. environment for drying for 22 hours to obtain a porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 450° C., and calcine for 3.5 hours to remove impurities, thereby obtaining impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, then add 2% of the mass of a silane coupling agent (3-aminopropyltriethylsilane) to the obtained mixture, mix thoroughly, then add 10% of the mass of a cross-linking agent citric acid to the mixture, use a sol-gel method, stir thoroughly, and then slowly drop ammonia water to the obtained mixture to adjust the pH to 9 to obtain a reaction sol for standby use; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry at 60°C for 24 hours to form a gel, then place the gel in a muffle furnace, set the temperature to 500°C, and calcine for 4 hours to obtain a finished high-selectivity catalyst.

[0031] Test verification The plastic polyethylene was subjected to catalytic pyrolysis reaction using the highly selective catalysts prepared in Examples 1 to 5 of the present invention and a comparative example (commercially available conventional alumina catalyst).

[0032] The catalytic performance and aromatic hydrocarbon yield of the high selectivity catalyst prepared in each example and the comparative example catalyst were measured.

[0033] The catalytic pyrolysis reaction temperatures of plastic polyethylene were set at 200°C, 250°C, 300°C, 350°C, and 400°C, respectively. The pyrolysis process was to weigh a certain amount of polyethylene film, mix the highly selective catalyst and conventional alumina catalyst prepared in each experimental example with polyethylene in the same proportion, put them into a pyrolysis reactor, and keep them at a preset temperature for a period of time to allow the polyethylene to be pyrolyzed under the action of the catalyst.

[0034] Finally, the highly selective catalyst products prepared in each example were analyzed by gas chromatography-mass spectrometry. The aromatics yields of each experimental example at different pyrolysis temperatures were determined as shown in the attached figure. Figure 1 shown.

[0035] Depend on Figure 1 It can be seen that: compared with the conventional alumina catalyst in the comparative example, the highly selective catalysts prepared in Examples 1 to 5 of the present invention have high selectivity for aromatic hydrocarbons; at the same time, when the pyrolysis temperature is 300°C, the activity of the conventional alumina catalyst is lower than that of the highly selective catalyst prepared in each example, and the highest activity point of the conventional alumina catalyst appears between 300°C and 400°C, but the decrease in the aromatic hydrocarbon yield from 350°C to 400°C is greater than the decrease in the catalyst prepared in other experimental examples. In a wide temperature range, its deactivation rate is fast and its life is short. In summary, the highly selective catalyst prepared in the examples solves the problems of low activity, short life, and insufficient selectivity of existing catalysts.

[0036] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly selective catalyst for plastic pyrolysis, characterized in that: The following steps are involved: Step 1, weigh wood pulp cellulose or cotton pulp cellulose and aluminum oxide as raw materials in a molar ratio of 1: (3-12) and set aside; Step 2: Soak the wood pulp cellulose and / or cotton pulp cellulose weighed in step 1 in a sodium hydroxide solution, and perform a porous treatment at a temperature of 70-90° C. for 1.5-3 hours. After taking out, rinse with deionized water until neutral, and then transfer to a 55-70° C. environment for drying for 20-25 hours to obtain porous cellulose for later use; Step 3: Place the aluminum oxide weighed in step 1 in a muffle furnace, set the temperature to 450-500° C., and calcine for 3-4 hours to obtain impurity-free aluminum oxide for later use; Step 4: Mix the porous cellulose obtained in step 2 with the impurity-removing alumina obtained in step 3, and add a silane coupling agent and a cross-linking agent citric acid to the obtained mixed materials in sequence, stir and mix thoroughly, and then drop ammonia water into the obtained mixed materials to adjust the pH value to 8-9, to obtain a reaction sol, which is set aside; Step 5: Transfer the reaction sol obtained in step 4 to an evaporating dish, evaporate and dry it at 60-65°C to form a gel, then place the gel in a muffle furnace, set the temperature to 450-500°C, and calcine it for 4-5h to obtain a finished high-selectivity catalyst.

2. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 1, the purity of the wood pulp cellulose or cotton pulp cellulose is not less than 98%.

3. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 1, the purity of the aluminum oxide is not less than 98%.

4. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 2, the mass concentration of the sodium hydroxide solution is 10%, and the sodium hydroxide solution is required to completely submerge the weighed wood pulp cellulose or cotton pulp cellulose.

5. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 2, the temperature of the pore-opening treatment is 80° C., and the treatment time is 2 hours.

6. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 4, the amount of the silane coupling agent added is 2% of the mass of the mixed material.

7. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 4, the amount of the cross-linking agent citric acid added is 6-10% of the mass of the mixed materials.

8. The method for preparing a highly selective catalyst for plastic pyrolysis according to claim 1, characterized in that: In step 5, the evaporation drying time is 20-24 hours.

9. A highly selective catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the highly selective catalyst according to claim 9 in catalyzing the pyrolysis of plastics.